2018
DOI: 10.1136/bcr-2018-224935
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of PTSD treatment through social support in Idobata-Nagaya community housing after Fukushima’s triple disaster

Abstract: Cognitive–behavioural therapy is a first-line treatment for post-traumatic stress disorder (PTSD), but it is difficult to implement in disaster settings. We report the case of an 80-year-old Japanese woman, who was diagnosed with PTSD after the 2011 triple disaster (earthquake, tsunami and nuclear plant accident) in Fukushima. Her recovery was greatly enhanced by the social support she received while living in Idobata-Nagaya community housing, established by Soma city in Fukushima, where residents could natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…In the case of an elderly woman with symptoms of PTSD caused by the tsunami, as reported by Hori et al, the recurrence was also caused by being involuntarily blamed for being involved in a severe conflict among residents in the communal dwelling where she was living. 23 Although our patient recovered from his mood disorder by using medication, he had two repeated flare-ups which led to the implementation of prolonged exposure therapy 16 17 -a psychotherapy focused on PTSD. North and Pfefferbaum have argued that less invasive treatments should be prioritised in the immediate aftermath of a disaster as an intervention for post-disaster PTSD, and specialised trauma-focused treatments should be provided only when depression and PTSD symptoms persist.…”
Section: Global Healthmentioning
confidence: 84%
See 1 more Smart Citation
“…In the case of an elderly woman with symptoms of PTSD caused by the tsunami, as reported by Hori et al, the recurrence was also caused by being involuntarily blamed for being involved in a severe conflict among residents in the communal dwelling where she was living. 23 Although our patient recovered from his mood disorder by using medication, he had two repeated flare-ups which led to the implementation of prolonged exposure therapy 16 17 -a psychotherapy focused on PTSD. North and Pfefferbaum have argued that less invasive treatments should be prioritised in the immediate aftermath of a disaster as an intervention for post-disaster PTSD, and specialised trauma-focused treatments should be provided only when depression and PTSD symptoms persist.…”
Section: Global Healthmentioning
confidence: 84%
“…In the case of an elderly woman with symptoms of PTSD caused by the tsunami, as reported by Hori et al , the recurrence was also caused by being involuntarily blamed for being involved in a severe conflict among residents in the communal dwelling where she was living. 23 …”
Section: Global Health Problem Analysismentioning
confidence: 99%
“…Such opportunities help them heal from the damage caused by the earthquake. [11] The same effects could not have been attained in nursing home facilities.…”
Section: Discussionmentioning
confidence: 97%
“…It is noteworthy that a positive social environment, including the attachment to intimate partners, is usually associated with better prognosis during treatment (DiGangi et al, 2013;Ferrer-Perez et al, 2019). Numerous clinical and animal studies have demonstrated the beneficial effect of social buffering on alleviating symptoms of PTSD (Kiyokawa et al, 2007;Hori et al, 2018;Charlson et al, 2019). Specifically, a variety of animal studies had focused on the contributions of social support from a same-sex unfamiliar partner during fear extinction training or retrieval test.…”
Section: Discussionmentioning
confidence: 99%